2015
DOI: 10.1007/s00259-015-3164-9
|View full text |Cite
|
Sign up to set email alerts
|

Baseline and ongoing PET-derived factors predict detrimental effect or potential utility of 18F-FDG PET/CT (FDG-PET/CT) performed for surveillance in asymptomatic lymphoma patients in first remission

Abstract: The present study confirms the need of restricting the use of surveillance PET/CT to patients at high risk of relapse. Information derived from PET/CT performed at baseline (metabolic disease burden), in the course (PET2) and at the end of therapy (unrelated hot spots) can help to select high-risk patients and also to identify patients more likely to present equivocal findings at PETsv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…For all 18 F-FDG PET/CT scans, the following 8 parameters were measured: maximum diameter of the primary lesion (T); maximum diameter of the largest lymph node (N); maximum diameter of the largest metastatic lesion (M); SUV max ; SUV mean ; size-incorporated SUV max (SIMaxSUV); MTV; and TLG. SUV max , SUV mean , SIMaxSUV, MTV, and average glycolytic volume were independently measured for T, N, and M. In particular, SIMaxSUV was defined as the product of the largest diameter (mm) of the primary lesion (for T) or of the largest lesion (for N and M) and the SUV max of the same lesion (16,17); MTV was assessed using a syngo (Siemens) workstation and was computed using an SUV max of greater than or equal to 2.5 as a threshold (10); and TLG for T, N, and M was computed as MTV • SUV mean .…”
Section: Image Analysismentioning
confidence: 99%
“…For all 18 F-FDG PET/CT scans, the following 8 parameters were measured: maximum diameter of the primary lesion (T); maximum diameter of the largest lymph node (N); maximum diameter of the largest metastatic lesion (M); SUV max ; SUV mean ; size-incorporated SUV max (SIMaxSUV); MTV; and TLG. SUV max , SUV mean , SIMaxSUV, MTV, and average glycolytic volume were independently measured for T, N, and M. In particular, SIMaxSUV was defined as the product of the largest diameter (mm) of the primary lesion (for T) or of the largest lesion (for N and M) and the SUV max of the same lesion (16,17); MTV was assessed using a syngo (Siemens) workstation and was computed using an SUV max of greater than or equal to 2.5 as a threshold (10); and TLG for T, N, and M was computed as MTV • SUV mean .…”
Section: Image Analysismentioning
confidence: 99%
“…19,20 Investigators examined the size-incorporated maximum standardized uptake value (SIMaxSUV), defined as the product of SUVmax and the greatest lesion diameter, and found that a high SIMaxSUV is the single most important predictor for disease-free survival and overall survival in DLBCL patients. 33 In the present study, ΔSUVmax*ΔSLD is defined as the change in the product of ΔSLD and ΔSUVmax, which is similar to the change in SIMaxSUV. ΔSLD is easily measured and reproducible.…”
Section: Discussionmentioning
confidence: 97%
“…Early identi cation of patients with DLBCL who are rapidly progressing under conventional therapy is needed to aid strati cation for innovative treatment. This requires an more adapted risk scoring method in which imaging features and genetic factors could play an important role together, according to recent research progress [1,11,14,25] . The current study is believed to be the rst to evaluate the relevance of combination of TMTV and SDmax calculated from the initial PET/CT ndings and genetic mutations obtained by NGS.…”
Section: Discussionmentioning
confidence: 99%
“…The 43 genes designed in a panel based on literature review of NGS studies in DLBCL [22][23][24][25] were as follows: ARID1B, ATM, B2M, BCL10, BCL2, BCL6, BTG1, CARD11, CCND3, CD58, CD79A, CD79B, CDKN2A, CIITA, CREBBP, EPHA7, EZH2, EP300, FAS, GNA13, IRF8, ITPKB, JAK2, KMT2C, KMT2D, MEF2B, MFHAS1, MYC, MYD88, NOTCH1, NOTCH2, PAX5, PIM1, PPM1D, SOCS1, SGK1, STAT3, STAT6, TET2, TNFAIP3, TNFRSF14, TP53, and XPO1. The lymphopanel was designed by KingMed.…”
Section: Ngs Data Analysismentioning
confidence: 99%